Cold snare defect protrusion and incomplete polyp resection after forced cold snare polypectomy: a prospective observational study - Arimoto, Jun; Chiba, Hideyuki; Yamada, Keiji; Nishiguchi, Takanori; Kobayashi, Mikio; Okada, Naoya; Suto, Takuma; Niikura, Toshihiro; Kuwabara, Hiroki; Nakaoka, Michiko; Ida, Tomonori (Endoscopy, 2023)
Background Cold snare defect protrusions (CSDPs) that occur after cold snare polypectomy (CSP) are considered indicators of incomplete polyp resection (IPR). We have sometimes experienced difficulty resecting polyps with snaring alone; in such cases, a forcible pull on the snare by the endoscopist is necessary. We call this procedure “forced CSP (FCSP).” However, no previous studies have evaluated this procedure. Methods This was a prospective observational study. From November 2020 to June 2021, the frequency, safety, and validity of FCSP were evaluated at our hospital. We distinguished CSP with snaring alone performed by the assistant as conventional CSP, and CSP requiring a forcible pull on the snare by the endoscopist as FCSP. Results Of 1315 polyps removed, 105 underwent FCSP (8%). The perforation rate was 0% in both groups. The rate of CSDP after the procedure was 96.2% (101/105) with FCSP and 6.4% (77/1210) with conventional CSP (P<0.001). The rate of IPR was 12.5% (13/104) with FCSP and 6.2% (75/1208) with conventional CSP (P=0.02). Multivariable analysis identified polyps located in the cecum (risk ratio [RR], 1.13; 95%CI 1.050–1.179; P=0.003) and polyps ≥6mm in diameter (RR, 2.37; 95%CI 2.146–2.542; P<0.001) as independent risk factors for FCSP.Conclusions FCSP was performed on 105 polyps (8%) in this study. FCSP may be associated with the occurrence of CSDP and IPR. Further studies are necessary to confirm our results.